Paul and the rise of the slave : death and resurrection of the oppressed in the epistle to the Romans - Bryant, K. Edwin. (Biblical Interpretation Series, 2016)
Paul and the Rise of the Slave locates Paul's description of himself as a "slave of Messiah Jesus" in the epistolary prescript of Paul's Epistle to Rome within the conceptual world of those who experienced the social reality of slavery in the first century C.E. The Althusserian concept of interpellation and the Life of Aesop are employed throughout as theoretical frameworks to enhance how Paul offered positive ways for slaves to imagine an existence apart from Roman power. An exegesis of Romans 6:12-23 seeks to reclaim the earliest reception of Romans as prophetic discourse aimed at an anti-Imperial response among slaves and lower class readers.